Skewfoot Deformity: State of the Art - Antonio Mazzotti; Federico Sgubbi; Alberto Arceri; Gianmarco Di Paola; Elena Artioli; Simone Ottavio Zielli; Lorenzo Marcucci; Nicola Guindani; Cesare Faldini; Maurizio De Pellegrin (Children)
Background: Skewfoot, also known as Z-foot, is a rare and complex deformity characterized by a combination of forefoot adduction and hindfoot valgus, resulting in a “Z” shape. Due to its rarity, diagnostic criteria and standardized treatment guidelines are lacking. This scoping review aims to systematically map and summarize the current knowledge regarding skewfoot. Methods: A comprehensive literature search of the PubMed, Cochrane Library, and Scopus databases was conducted to identify relevant articles. Patient-specific data were meticulously extracted from eligible studies and analyzed in detail. Results: A total of 12 studies met the inclusion criteria. Each study was independently reviewed, and data on epidemiology, etiology, clinical presentation, imaging assessment, and treatment options were extracted. Conclusions: The true incidence of skewfoot remains unknown. Etiology is likely multifactorial, often associated with systemic and neurological disorders. Skewfoot management ranges from conservative approaches to surgery. A medial cuneiform opening wedge osteotomy is the most used technique; however, the frequent need for additional procedures emphasizes the complexity of the deformity and the importance of a personalized approach.